Rotation Invariant Face Recognition Using Radial Harmonic Fourier Moments (Journal of the College of Basic Education, 2022)
Face recognition is one of the most important tasks in the biometric domain which still receive more concern due to its immense variety of applications. Face recognition has a lot of challenges, one of these challenges is the rotation variation which highly affects the accuracy of the face recognition task. In this paper, we have proposed rotational invariant face recognition technique based on radial harmonic Fourier moments which have the ability to provide global rotation invariant features. The proposed method’s accuracy evaluated by carried out extensive experiments using two of the standard databases which are ORL and JAFFE. The results of these experiments indicated that the proposed method is rotation invariant and achieved high recognition rates in the presence of different variations.